Analisis Break Event Point Sebagai Alat Untuk Menentukan Komposisi Penjualan Dalam Pencapaian Target Laba (Studi Kasus pada CV. Sinar Logam di Natar Lampung Selatan) - M. Yusuf Sulfarano Barusman; . Farlina; Evi Ekawati (Jurnal Akuntansi dan Keuangan, 2010)
The research aims to determine the role of Break Even Point Analysis in determining the composition of sales in the achievement of profit targets of various products produced and sold by CV. Metal beams. While the usefulness of the research is to contribute ideas to the company in determining the composition of sales, while deepening science writers get obtained by comparing theory with the practice of the company. Of the above problems, the hypothesis: "Break Even Point Analysis can help a company to determine the exact composition of sales in order to achieve earnings targets."The research method consisted of the study variables and operationalization of variables, types and sources of data, as well as methods of data collection. Analysis tool used is the qualitative analysis and kuantitatif.Perencanaan composition formed during the sales mix is not achieving the desired profit target because the enterprise in planning the composition of sales is not based on analysis of the Break Even Point, but is affected by the mechanism and market conditions.